Edukasi Seks Dan Gizi Adaptif Untuk Meningkatkan Kesiapan Pubertas Pra-Remaja Di Wilayah Pesisir Tarakan - Eka Darmayanti Putri Siregar; Mega Octamelia; Reza Bintangdari Johan; Nur Citra; Selvia Febrianti; Andi Sri Hastuti Handayani Usman; Rizky Vaira; Annisa Eka Permatasari; Desy Putri Nabila; Clodya Puspita Sari (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
The transitional stage of puberty is often accompanied by limited understanding of reproductive health and inadequate literacy on balanced nutrition, conditions that may increase vulnerability to risky behaviours and impair healthy development. This study aimed to strengthen pre-adolescents’ knowledge of reproductive health and adaptive nutrition through interactive school-based education. The intervention was implemented at SD Negeri 047 Tanjung Pasir, East Tarakan, involving 52 sixth-grade students who completed pretest–post-test assessments. Educational materials were delivered using leaflets, posters, and two-way interactive discussion. Knowledge outcomes were analysed descriptively and changes in proportions. The results demonstrated a meaningful improvement in students’ knowledge of reproductive health, with the proportion of high-category scores increasing from 57.7% to 67.3% (effect size +9.6%). Knowledge of adaptive nutrition also increased, although to a lesser extent, from 61.5% to 63.5% (effect size +3.2%). The largest gains were observed in the ability to identify reproductive organs, recognize pubertal changes, and understand appropriate personal boundaries. These findings indicate that visual-supported, interactive education is particularly effective in enhancing pubertal literacy among pre-adolescents, even in coastal settings where discussions about sexuality may be culturally sensitive. This study offers novelty by highlighting how context-adapted reproductive and nutrition education can be successfully implemented in a coastal elementary school environment. The implications for practice include the need for schools to integrate continuous reproductive health and nutrition education into routine learning and to strengthen collaboration with teachers, community health centres, and parents to reinforce healthy behaviours among pre-adolescents.